ICAM-1 gene rs5498 polymorphism decreases the risk of coronary artery disease - Liu, Ailing (Medicine (Baltimore), 2018)
BACKGROUND: Many studies investigated the association between intercellular adhesion molecule 1 (ICAM-1) gene rs5498 polymorphism and the risk of coronary artery disease (CAD). However, the results were inconsistent. METHODS: To clarify convincing association, we conducted a comprehensive meta-analysis by searching in PubMed, Embase, Web of sciences, Sciences citation index, Google scholar, Cochrane Library, and the CNKI databases. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. RESULTS: A total of 29 case–control studies with 5,494 cases and 6,364 controls for rs5498 polymorphism were included. The studied populations of this meta-analysis included Caucasians and Asians. Meta-analysis showed that rs5498 polymorphism was associated with the decreased risk of CAD. Stratification analysis of ethnicity found that rs5498 polymorphism decreased the risk of CAD among Caucasians, but not among Asians. Stratification by type of CAD revealed that ICAM-1 gene rs5498 polymorphism was also correlated with the decreased risk of myocardial infarction (MI). CONCLUSION: In conclusion, this meta-analysis indicates that ICAM-1 gene rs5498 polymorphism decreases the risk of CAD.